(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The paper deals with the Polish-Ukrainian borderland and its image in the lit-erature of the second half of the 20th century. I investigate the process of mythologiza-tion of that space in the memory of authors who had spent their childhood there.